Efek Senam Yoga dan Poundfit Terhadap Kualitas Tidur Wanita Usia 30 – 40 Tahun - Damayanti, Dhita Azzahra; Yuliastrid, Dita; Kumaat, Noortje Anita; Noordia, Anna (Jurnal Porkes, 2024)
Sleep quality is a person's level of satisfaction with their sleep. 43.7% of the Indonesian population aged > 19 years has a poor level of sleep quality. The purpose of this study was to examine the effect of yoga and poundfit exercises on sleep quality, and to determine the comparison of the effect between yoga and poundfit exercises on sleep quality in women aged 30-40 years. The method uses a pretest-posttest group design with a quantitative descriptive approach. The sample was determined using purposive sampling technique with a total of 14 samples with the criteria of women aged 30-40 years with normal BMI. Pittsburgh sleep quality index (PSQI) questionnaire. Samples received yoga and poundfit interventions with a duration of 45 - 60 minutes / day for 3x / week in 1 month. The results of the effect test using the paired t test obtained the results of p 0.008 <0.05 for the yoga exercise group and p 0.006 <0.05 for the poundfit group, so the results showed that there was an effect of yoga exercises and poundfit on sleep quality. Comparison test using independent t-test with the results of p 0.951> 0.05, it can be concluded that there is no difference in the influence between yoga and poundfit groups on sleep quality in women aged 30-40 years.